The Fractured Right to Vote: Democracy, Discretion, and Designing Electoral Districts - Pal, Michael (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
Electoral boundary commissions and Parliament have recently transformed Canada’s federal electoral map. The 2015 federal election was contested on a new map of 338 ridings, after 30 seats were added to the House of Commons by the Fair Representation Act and commissions set the boundaries of each district. The introduction of independent, non-partisan commissions in 1964 to draw the maps has achieved great success in eliminating the previously entrenched practice of gerrymandering. The extensive discretion granted to commissions to set boundaries, however, generates a new series of potential problems that can undermine the fairness of the electoral map.This article takes the new map as an opportune time to analyze the Canadian experience with electoral boundary commissions and, particularly, their exercise of discretionary authority. It demonstrates that the ten provincial commissions have adopted divergent approaches to their common task of establishing electoral boundaries. The commissions are at times in direct conflict with one another on the meaning and scope of fundamental principles of redistricting, such as representation by population, community of interest, and minority representation. These conflicting approaches have gone beyond reasonable disagreements over the specific content of the relevant legislative and constitutional principles. The exercise of the discretion held by the commissions in these competing ways has frustrated the principle of the political equality of all citizens. This article argues that the discretion granted to Canadian electoral boundary commissions should be restructured in order to better achieve a common realization of the right to vote.